Quantification of a Facility Radiological Security Risk Index With a Graphical User Interface Tool - Rane, Shraddha; Harris, Jason T (Health physics (1958), 2022)
Healthcare facilities around the world routinely use radioactive sources to diagnose and treat illness. To effectively manage the security of radioactive sources, these facilities need to understand the risk, which is comprised of threat, vulnerability, and consequences. The threat component of risk requires knowledge of potential adversaries and understanding their capabilities and intentions. To help articulate the multiple layers of threat and support better informed decisions, the research developed a risk-based methodology to evaluate radiological security at the facility level. The methodology is applied to a radiological dispersal device (RDD) incident from three radionuclides of concern: 137Cs, 60Co, and 192Ir. The results of the research have led to the creation of a potential facility risk index (PFRI). The PFRI is mathematically represented as the exponential product of the maximum expected utility among the threat groups, the sum of geographic vulnerability and cultural vulnerability, and net consequences. The PFRI is a novel risk index that quantifies the facility risk on a scale of 1 to 10, 1 being "very low risk" and 10 being "very high risk." A MATLAB-based graphical user interface (GUI) tool was also developed to enable the radiological facility (i.e., healthcare facility) staff to conduct self-assessments and manage their most valuable assets. The PFRI methodology is a useful starting point for any healthcare facility risk assessment and is a valuable input for decision makers considering potential investments in security upgrades.